An effective Hamiltonian approach for Donor-Bridge-Acceptor electronic transitions: Exploring the role of bath memory - E.R. Bittner (Condensed Matter Physics, 2016)
We present here a formally exact model for electronic transitions between an initial (donor) and final (acceptor) states linked by an intermediate (bridge) state. Our model incorporates a common set of vibrational modes that are coupled to the donor, bridge, and acceptor states and serves as a dissipative bath that destroys quantum coherence between the donor and acceptor. Taking the memory time of the bath as a free parameter, we calculate transition rates for a heuristic 3-state/2 mode Hamiltonian system parameterized to represent the energetics and couplings in a typical organic photovoltaic system. Our results indicate that if the memory time of the bath is of the order of 10-100 fs, a two-state kinetic (i.e., incoherent hopping) model will grossly underestimate overall transition rate.